Identification of woods from museum archaeological collections: use of local and non-local wood in pre-Columbian societies from northwestern Argentina - Sprovieri, Marina Leticia (2019)
Archaeological finds of uncharred wooden artefacts are particularly rare in Northwestern Argentina. In this respect, the museum collections from the sites of La Paya and El Churcal, in the Calchaqui Valley (Northwestern Argentina), are significant owing to their excellent conservation and diversity of their uncharred wooden artifacts. However, due to necessary current conservation policy in Argentina, researchers may have limited access to artifacts and sampling possibilities. We carried out the identification of woods used to manufacture artifacts from La Paya and El Churcal collections as part of our ongoing studies on the processes of production, circulation, and consumption of raw materials and goods in societies inhabiting the Calchaqui Valley during the late pre-Columbian period (ninth to sixteenth centuries). As a result, we acquired previously unknown information on woods used to manufacture artifacts in the Calchaqui Valley. Despite working with two museum collections that offered different possibilities for intervention and different levels of accuracy of identification, we were able to obtain successful results that show similar trends between the collections.